Effect of Internal Green Marketing Mix Elements on Customers’ Satisfaction in Jordan: Mu’tah University Students - Al-Majali, Malek; Tarabieh, Saeed (Jordan Journal of Business Administration, 2020)
This paper aims at investigating the effect of internal green marketing mix elements on Mu’tah University students’ satisfaction in Jordan. This study is based on quantitative approach methodology to collect the primary data. The researchers developed a questionnaire to measure the study constructs, which included 27 items. Five hundred questionnaire forms were distributed to the study sample. Four hundred and seventy-five (475) questionnaire forms were valid for analysis. Some analysis tests, such as data screening, data descriptive testing, reliability and hypothesis testing, were conducted using SPSS, v. 20 and AMOS, v. 16. The results of this study indicated that there are seven supported hypotheses related to green product, green price, green place, green promotion, green provided information, green process and green people, respectively. But, one hypothesis related to green policy was not supported. Finally, some recommendations presented in this study targeted academics and decision makers in Jordan in this filed.